Soccer small-sided games in young players: rule modification to induce higher physiological responses - Halouani, J.; Chtourou, H.; Dellal, A.; Chaouachi, A.; Chamari, K. (Biology of Sport, 2017)
The aim of this study was to identify the physiological responses of 3 forms of players' numbers during two different games rules of small-sided games (SSG: stop-ball vs. small-goals rules). Eighteen youth amateur soccer players (age 13.5±0.7 years; height 168.9±6.1cm; body mass 63.1±7.7 kg) participated in this study and performed 3 SSGs with varying players' number (2vs.2; 3vs.3 and 4vs.4): stop-ball SSG (SB-SSG) vs. small-goals SSG (SG-SSG) in a randomized and counter-balanced order on a constant pitch dimension (20×25m). The players performed 4×4 min SSG with 2-min of passive recovery in-between. Heart rate (HR), (expressed in bpm and % HRmax), lactate ([La-]), and rating of perceived exertion (RPE) were collected during each session. SB-SSG induced the higher HR values in comparison with the SG-SSG for the 3 game formats (2vs.2; 3vs.3 and 4vs.4). Also, compared with SG-SSG, SB-SSG induced the higher HR values during 2vs.2 compared with 4vs.4 games rules (178 vs. 174 and 175 vs. 171 bpm, respectively). However, the SB-SSG was more intense compared with SG-SSG in the 2 vs. 2 game rule compared with the two others (3 vs.3 and 4 vs. 4) for [La-] and RPE (7.58 vs. 7; 7.25 vs. 6.75 and 6.5 vs. 6.16 mmol L-1, and 7.75 vs. 7.33; 7.41 vs. 7.08 and 7.16 vs. 6.83, respectively). Therefore, the use of 2 vs. 2 and 3 vs. 3 SSG with SB-SSG seems to represent an alternative to coaches to increase cardiovascular and metabolic demands in youth soccer players.